2007
DOI: 10.1186/1743-0003-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Human-robot cooperative movement training: Learning a novel sensory motor transformation during walking with robotic assistance-as-needed

Abstract: Background: A prevailing paradigm of physical rehabilitation following neurologic injury is to "assist-asneeded" in completing desired movements. Several research groups are attempting to automate this principle with robotic movement training devices and patient cooperative algorithms that encourage voluntary participation. These attempts are currently not based on computational models of motor learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 30 publications
2
105
0
3
Order By: Relevance
“…Es necesario tener en cuenta que el error de posición causado por el humano, es de hecho una característica deseable, que ayuda a potenciar el aprendizaje motriz humano (Emken et al, 2007), (Patton et al, 2006).…”
Section: Juego De Rehabilitación Virtual (Activo Asistido)unclassified
“…Es necesario tener en cuenta que el error de posición causado por el humano, es de hecho una característica deseable, que ayuda a potenciar el aprendizaje motriz humano (Emken et al, 2007), (Patton et al, 2006).…”
Section: Juego De Rehabilitación Virtual (Activo Asistido)unclassified
“…Further, it can be shown that such a learning law is used by the human motor system to overcome a predictable disturbance during reaching and walking [15], and further, that it minimizes a cost-function with error and effort terms [21]. The problem of robotic assistance-as-needed can similarly be posed as an optimization problem: minimize kinematic error, but also minimize robotic assistance force [22]. An error-based learning law with forgetting like (1) is one way to achieve this minimization [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The problem of robotic assistance-as-needed can similarly be posed as an optimization problem: minimize kinematic error, but also minimize robotic assistance force [22]. An error-based learning law with forgetting like (1) is one way to achieve this minimization [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work in robotic assistance has focused on developing sophisticated robotic mechanisms in order to support movement training of more complex movements such as walking [1][2][3][4]. Although robotic locomotor training has been proposed as a promising technique to improve rehabilitation in patients with severe gait impairments, the functional gains obtained after robotic training are still limited [5,6].…”
Section: Introductionmentioning
confidence: 99%